Answer:
-1.22 m/s
Step-by-step explanation:
To find the initial velocity, we will use the following equation:
![d=(1)/(2)(v_i+v_f)t](https://img.qammunity.org/2023/formulas/physics/college/902vzzs6n8fbcdepk91ke1bx2xscoe95mu.png)
Where d is the displacement, t is the time, vi is the initial velocity and vf is the final velocity.
So, replacing vf by 7.8 m/s, t by 5.7s, and d by 18.75 m, we get:
![18.75=(1)/(2)(v_i+7.8)(5.7)](https://img.qammunity.org/2023/formulas/physics/college/sca6v0bp0d5l3hhw3j1se7pd21vre4xqnm.png)
Now, we can solve for vi:
![\begin{gathered} (18.75)/(5.7)=(1)/(2)(v_i+7.8) \\ 3.29=(1)/(2)(v_i+7.8) \\ 3.29*2=v_i+7.8 \\ 6.58=v_i+7.8 \\ 6.58-7.8=v_i \\ -1.22m/s=v_i \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/6xa2hmah05ckbp48pnsi5jhywv82n4zfmy.png)
Therefore, the initial velocity of the bike was -1.22 m/s